1999
DOI: 10.1080/00071669987746
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone plasma concentration in male mule ducks: Effects of sampling sites, repeated samplings and ACTH injections

Abstract: 1. Changes in plasma corticosterone concentrations according to puncture sites and various challenges including injections of an ACTH agonist (Immediate Synacthen) were investigated in male mule ducks. 2. Lower concentrations were measured in samples drawn by puncture from the occipital sinus than at a wing vein site. 3. Immobilisation and a single intramuscular injection of saline solution (1 ml, 0.9%) had no effect on plasma corticosterone after 15 min. 4. A single intramuscular injection of ACTH (5 microg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…injection of 10 µg per hen (approximately 5 µg·kg -1 BW) 1-24 ACTH (Immediate Synacthen, Norvatis, 2 and 4 rue Lionel Terray, BP 308, F-92506 Rueil Malmaison Cedex) diluted in saline solution (400 µL, 0.9% NaCl w/v). This dose has been shown to induce maximal HPA reactivity 15 min post injection in both laying hens (unpublished data) and in other bird species (ducks, [40]; turkeys and quails, unpublished data). Blood samples (3 mL) were collected from the wing vein into heparinised tubes prior to the injection and 15 min post-injection and the hens were placed in a crate during the period between the two samplings.…”
Section: Adrenal Responsivenessmentioning
confidence: 99%
“…injection of 10 µg per hen (approximately 5 µg·kg -1 BW) 1-24 ACTH (Immediate Synacthen, Norvatis, 2 and 4 rue Lionel Terray, BP 308, F-92506 Rueil Malmaison Cedex) diluted in saline solution (400 µL, 0.9% NaCl w/v). This dose has been shown to induce maximal HPA reactivity 15 min post injection in both laying hens (unpublished data) and in other bird species (ducks, [40]; turkeys and quails, unpublished data). Blood samples (3 mL) were collected from the wing vein into heparinised tubes prior to the injection and 15 min post-injection and the hens were placed in a crate during the period between the two samplings.…”
Section: Adrenal Responsivenessmentioning
confidence: 99%
“…The present experiments were thus undertaken in continuation of previous studies [13,27] to first investigate further HPAaxis functionality in male mule ducks and having this information in hand, to check for the possible interactions between force-feeding practice and rearing environment on behavioural and physiological indicators of stress and poor welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, manipulation such as catching and handling has been shown to induce stress responses, reflected by rises in corticosterone levels in chickens [19,24], quails [28], turkeys [14] and ducks [27]. However, the results from a previously published study [13] showed that force-feeding per se does not induce any consistent increase in corticosterone levels and did not provide any indication that it leads to a chronic stress state, whereas the adrenal glands are fully responsive to ACTH challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The 10 min delay after ACTH treatment was chosen because it has been previously shown that it allowed maximal CORT level to be reached in ducks (Noirault et al, 1999). Plasma was separated by centrifugation and kept at 2208C prior to analysis.…”
Section: Physiological Measuresmentioning
confidence: 99%
“…Injection of a high dose of 1-24 ACTH allows to assess maximal secretion capacity from the adrenal glands (Harvey et al, 1980). Conversely, initial CORT level is very sensitive to environmental condition (Noirault et al, 1999) and may partly result from a sensibility to capture. Behavioural tests involved different features including coping with new -E-mail: guemene@tours.inra.fr environment, social isolation, specific response towards human and antipredator strategy.…”
Section: Introductionmentioning
confidence: 99%